TRIP database 2.0: a manually curated information hub for accessing TRP channel interaction network. - Young-Cheul Shin (Public Library of Science (PLoS), 2012)
Transient receptor potential (TRP) channels are a family of Ca(2+)-permeable cation channels that play a crucial role in biological and disease processes. To advance TRP channel research, we previously created the TRIP (TRansient receptor potential channel-Interacting Protein) Database, a manually curated database that compiles scattered information on TRP channel protein-protein interactions (PPIs). However, the database needs to be improved for information accessibility and data utilization. Here, we present the TRIP Database 2.0 (http://www.trpchannel.org) in which many helpful, user-friendly web interfaces have been developed to facilitate knowledge acquisition and inspire new approaches to studying TRP channel functions: 1) the PPI information found in the supplementary data of referred articles was curated; 2) the PPI summary matrix enables users to intuitively grasp overall PPI information; 3) the search capability has been expanded to retrieve information from 'PubMed' and 'PIE the search' (a specialized search engine for PPI-related articles); and 4) the PPI data are available as sif files for network visualization and analysis using 'Cytoscape'. Therefore, our TRIP Database 2.0 is an information hub that works toward advancing data-driven TRP channel research.